The grandiose structures of the Sabeans of Harran - حسب الله علوان محمد (Journal of College of Education, 2021)
The study of places of worship in any religion is an important focus to learn about this religion and to know the nature of its beliefs and the rituals, secrets and religious practices associated with it worthy of research and follow-up, including the (venerable structures) of the Sabeans of Harran, whose performance was linked to their belief that the planets are the masterminds of the world and the impossibility of reaching the last because it is far and You see with the eye, so it is necessary to have a mediator on whose behalf it is possible to resort to it within its own rituals and secrets. These structures occupied a large area of interest among the Sabeans of Harran in general and among some Muslim historians in particular, who found in the follow-up of these places and the rituals and issues they contained that brought them closer to knowledge of the Sabeans of Harran in terms of knowledge of their name and the historical conditions that accompanied that and the diagnosis of their beliefs and places of worship And their locations, names, and their designation as (grandiose structures) as an indication of their religious importance and monitoring and following up on the things that happen within these structures. These structures included a number of images and idols that represented the planets, and each bore a name for a specific planet that differed in its shapes and minerals that were painted, as it was the special place for the rituals of these planets, which are called (the five secrets), which priests and their assistants throw on the little children inside these structures And in private basements prepared for these rituals. The research included an introduction, two papers and a conclusion. The first topic addressed the research on naming and beliefs (Sabena’s of Harran), and the second topic was devoted to studying the emergence of structures, their locations, design, names and rituals, and a conclusion in which he recorded the most important results that we have